Guillain–Barré syndrome post-SARS-CoV-2 vaccine: a systematic review and data analysis on its clinical, laboratory, electrophysiological, and radiological features - Hadhiah, Kawther; Alhashim, Ali; Al-Dandan, Hassan A.; Alhassan, Eman; Alqarni, Abdulaziz M.; Memish, Abdullah Adil A.; Alabdali, Majed (Frontiers in Neurology, 2024)
Introduction Guillain–Barré syndrome (GBS) is a rare disease that affects almost 0.8–1.9 cases per 100,000 people worldwide every year. This is the most prevalent cause of subacute flaccid paralyzing illness today. It is a subacute inflammatory demyelinating polyradiculoneuropathy; the typical scenario involves ascending symmetrical flaccid paralysis, but in some circumstances, sensory, autonomic, and cranial neuropathy may also be involved. Several vaccines have been found to have complications since the previous century. Numerous case reports of GBS in the literature have been reported following COVID-19 vaccines in recent times. Objective This study aimed to conduct a comprehensive examination of GBS cases that have been reported after COVID-19 vaccines; to analyze the descriptive statistical analysis of data gathered regarding clinical, laboratory, electrophysiological, and radiological characteristics; to discuss, based on the available evidence, whether the disease has a preference for a particular vaccine type; and to speculate on the potential pathogenesis. Methodology This review has been carried out by recommendations of the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Result Reviewing 60 case reports illustrated that most of them are from the USA (18.1%) and the majority of affected individuals were males (60%). The results favored the association between vector-based SARS-CoV-2 vaccine, particularly AstraZeneca vaccine, and the GBS. The mean of symptoms onset is 11.4 days. The results of diagnostic tests such as LP are consistent mostly with albumin-cytological dissociation (81.81%), where brain and spine MRI was unremarkable in 59.52%. Regarding electrodiagnostic tests, AIDP is the most common variant (61.81%). The management was not consistent among the case reports. However, IVIG is the most frequent way of treating these patients (68.33%). The functional outcome was documented in 47 patients; 65% improved with medical management. Conclusion This study aimed to conduct a systematic review of reported cases of GBS following COVID-19 vaccines and descriptive statistical analysis of collected data on clinical, laboratory, electrophysiological, and radiological features, to discuss, based on available results, whether the disease has a predilection to a specific vaccine type and to speculate the potential pathogenesis.